Potencial anticâncer da piplartina e da piperina, amidas isoladas de plantas do gênero piper - Bezerra, Daniel Pereira (2005)
Piplartine and piperine are alkaloids/amides isolated from Piper species. The activity of these compounds was initially evaluated on the brine shrimp lethality assay, sea urchin development, MTT assay using tumor cell lines, and hemolytic assay. Piperine showed a higher toxicity in brine shrimp than piplartine. Both piplartine and piperine inhibited the sea urchin development, but in this assay piplartine was more potent than piperine. In MTT assay, piplartine was also the most active with IC50 values ranging from 0.7 to 1.7 µg/mL. None of the tested substances induced hemolysis. Since the piplartine showed the best results, its mode of action was studied. Viability of HL-60, K562, JUKART, and MOLT-4 cell lines were affected by piplartine only after an exposure time of 24h, as analyzed by the Trypan blue exclusion. Piplatine reduced the number of viable cells associated with an increasing of the number of non-viable cells, which corroborate data from morphologic analysis. The cytotoxic activity of piplartine was related to the inhibition of DNA synthesis, as revealed by the reduction of BrdU incorporation. Administration of piplartine or piperine (50 or 100 mg/kg/day) inhibited the solid tumor development in mice transplanted with Sarcoma 180. The inhibition rates were of 28.7 and 52.3% for piplartine and 55.1 and 56.8% for piperine at lowest and highest dose, respectively. Piplartine-antitumor activity was related to the tumor proliferation rate inhibition, as observed by reduction of Ki67 staining in tumor of the treated-animals. The histopathological analysis of liver and kidney showed that both organs were reversible affected by piplartine and piperine treatment, but in a different way. Piperine was more toxic to the liver while piplartine affected more the kidney. Thus, both amides may act as antitumor agents, although, they seem to act through different pathways. Piplartine activity seems to be related to direct cytotoxicity on tumor cells, while piperine presented a host mediated activity.